PERENCANAAN BISNIS PADA USAHA TOKO ONLINE PLANET PLASTIK DAN DISTRIK PLASTIK - Kwan, Liyon; Ikhram W., M. Abdi Dzil (Jurnal Kewirausahaan dan Inovasi, 2022)
Increments in the number of e-Commerce buyers have opened more opportunities for entrepreneurs to engage in online businesses. However, the chances have urged them to create accurate business strategies and management in order to stay ahead in the market. Therefore, business planning must be made to help the companies go according to the right direction to attain their goals. Planet Plastik and Distrik Plastik are dropshipping companies; their entire operations are held in e- commerce. They provide various HDPE and PET plastic packaging. The analysis in this business planning covers the aspects of marketing, organization and management, production, and finance. The business feasibility assessments were based on the payback period calculation of three months and 23 days, net present value of IDR 10,269,323; profitability index of 2.22, and internal rate return of 45.9%. the profit analysis resulted in the break-even point of IDR 95,767,195 and contribution margin of 9.45%.